Potential Use of Instagram as Learning Tools in Improving EFL Students` Descriptive Writing Skill - May Lien Tia Candra, Ariesta; Ivan, Nurseha (Journal of Education and Religious Studies, 2025)
The study aims to find out how is the writing descriptive text developed by using Instagram at the EFL students of SMP NU Gendong and how is the response of the students in learning descriptive text through Instagram. In this study, the researcher focuses in improving the writing descriptive text by using Instagram. The subjects of this research are limited at the teacher and third grade of SMP NU Gendong.  This study used Design Development Research but employed in two approach that is quantitative and qualitative to analyze the data. The technique used by researcher to collect the data were interviews and questionnaires. The result of this study showed that applying Instagram helps the students to improve their idea before writing a descriptive text by applying Instagram. They prefer to write descriptive text in a caption than writing in their book. Data collected from the students’ response showed strong positive response from the participants that the application Instagram was good because they can help the students improve their ability in writing descriptive text. And also, they were excited in teaching and learning process. Students also showed good interest during the treatment. They were actively worked in their group and collaborated each other. They confidently write their opinion and were interested to do the student worksheets.